Instructional leadership practices and teachers’ job performance at high-performing vocational schools in Indonesia: a conceptual framework / Dita Puruwita, Leele Susana Jamian and Norazah Abdul Aziz - Puruwita, Dita; Jamian, Leele Susana; Abdul Aziz, Norazah (Universiti Teknologi MARA, 2022)
Job performance has long been regarded as an important factor and has become a significant indicator in determining the efficiency and effectiveness of the performance of numerous organisations. This is because an organisation's ability to sustain its operation and achieve organisational goals would depend on the performance levels of its employees, including institutions in educational settings. This paper draws from an ongoing doctoral study that aims to investigate the relationship between instructional leadership practices and teachers’ job performance at highperforming vocational schools in Indonesia. This paper also discussed the issues and concepts of both aforementioned variables in past studies that could assist in constructing the conceptual framework. Although past literature in global settings had postulated a potential relationship between instructional leadership practices and job performance, there is still limited research in the relevant topic when high-performing vocational schools is concerned. As to date, little empirical data was collected concerning the aforementioned relationship in local high-performing vocational schools in Indonesia. Therefore, researchers of this study embarked on the topic presenting problems and research gaps which eventually help to construct the conceptual framework of the two variables and their relationship.